Dynamics of the content of protein, lipids and glycogen in the organs and tissues of pike perch of the Kremenchuk reservoir in the pre-spawning and feeding periods - Yevtushenko, N.Yu.; Rudyk-Leuska, N.Ya.; Leuskyi, M.V. (Reports of the National Academy of Sciences of Ukraine, 2023)
In the pre-spawning period, there is a much lower level of total lipids in the liver compared to the feeding period, but a much higher level of glycogen. However, the available energy resources of the body, in our opinion, are sufficient to ensure plastic and generative metabolism associated with the trophoplasmic growth of oocytes on the eve of the spawning process. In general, the results of the research may indicate optimal environmental conditions and a sufficient level of development of forage objects in the aquatic environment of Kremenchuk Reservoir, which provide a high level of metabolic processes in the body of mature pike perch in feeding and prespawning periods of the annual cycle.